New headway Academic skills reading, writing, and study skills teacher's guide - Philpot, Sarah (New york Oxford university, 2007)
The course focuses on reading, writing, and study skills, including those required for vocabulary development and for undertaking research
Contents : language for writing - vocabulary development - language for speaking
12
Keywords: English language; Reading materials; Vocabulary